2020
DOI: 10.1055/s-0040-1719018
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Musculoskeletal Cancer Using Whole-Body Magnetic Resonance Imaging

Abstract: Whole-body magnetic resonance imaging (WB-MRI) is gradually being integrated into clinical pathways for the detection, characterization, and staging of malignant tumors including those arising in the musculoskeletal (MSK) system. Although further developments and research are needed, it is now recognized that WB-MRI enables reliable, sensitive, and specific detection and quantification of disease burden, with clinical applications for a variety of disease types and a particular application for skeletal involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 114 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…WB-MRI is increasingly used in screening for and characterization of MSK malignancy, as well as in tumor syndromes and marrow disorders. 19,23 Acquisition utilizing 3D techniques facilitates the acquisition of WB-MRI in a reasonable time period, as discussed previously. With regard to diagnostic performance, VIBE and WB-DWI were shown to be feasible and useful in the characterization of peripheral nerve tumors.…”
Section: Image Interpretation Advantagesmentioning
confidence: 99%
“…WB-MRI is increasingly used in screening for and characterization of MSK malignancy, as well as in tumor syndromes and marrow disorders. 19,23 Acquisition utilizing 3D techniques facilitates the acquisition of WB-MRI in a reasonable time period, as discussed previously. With regard to diagnostic performance, VIBE and WB-DWI were shown to be feasible and useful in the characterization of peripheral nerve tumors.…”
Section: Image Interpretation Advantagesmentioning
confidence: 99%
“…Whole-body (WB)-MRI with DWI can help detect bone marrow malignancies including multiple myeloma and metastatic disease and soft tissue neoplasms. 89,90 Sun et al showed the efficacy of WB-MRI with DWI in differentiating the various bone marrow infiltration patterns of monoclonal plasma cell diseases and also reported the association of ADC values with serum β2-microglobulin levels (indicator of tumor burden) in different bone marrow infiltration patterns among myeloma patients. 91,92 WB-MRI with DWI sequences has further shown diagnostic merit to evaluate treatment response in multiple myeloma patients, without the use of intravenous contrast.…”
Section: Whole-body Magnetic Resonance Imaging Biomarkersmentioning
confidence: 99%
“…In our practice, MRI is performed in all patients to assess the response to the intervention and/or plan further treatments. 18,30,31 In addition to MRI, to merely estimate the response to therapy and to detect progression or local or distant recurrence early on, hybrid imaging techniques, such as positron emission tomography (PET)/CT and PET/MRI, are sufficient and highly specific for this purpose. 31 Primary tumors of the spine, for instance, giant cell tumors, chordoma, chondrosarcoma, and osteosarcoma (►Fig.…”
Section: Presumed Malignancymentioning
confidence: 99%
“…18,30,31 In addition to MRI, to merely estimate the response to therapy and to detect progression or local or distant recurrence early on, hybrid imaging techniques, such as positron emission tomography (PET)/CT and PET/MRI, are sufficient and highly specific for this purpose. 31 Primary tumors of the spine, for instance, giant cell tumors, chordoma, chondrosarcoma, and osteosarcoma (►Fig. 8), are uncommon and represent < 5% of all bone neoplasms when compared with secondary metastatic disease, multiple myeloma, and lymphoma.…”
Section: Presumed Malignancymentioning
confidence: 99%
See 1 more Smart Citation